Las artes plásticas en el desarrollo de las habilidades cognitivas en los estudiantes con necesidades educativas especiales - Orrala Lino, Jennifer Paola (2021)
The present research arose from the educational need evidenced in the School of Basic Fiscal Education "José Elías Altamirano", located in the sector of La Floresta, of the province of Guayas, Guayaquil canton; in which it was observed that the students of the elementary sublevel present difficulties to solve mathematical logical operations, additions and subtractions correctly. Therefore, it is manifested that the proposal of the Plastic Arts plays a fundamental role to emerge, provide knowledge and the development of skills in students with special educational needs not associated with a disability, within the educational spaces, because it promotes experiences and learning where it allows the learner to receive the information and codify it in an appropriate way. The present work determined the importance of the development of cognitive skills in the students of the second year of Basic General Education with dyscalculia through the plastic arts...........